2022
DOI: 10.1002/anie.202201136
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised Cofactor Mimics for Interactome Discovery and Beyond

Abstract: Cofactors are required for almost half of all enzyme reactions, but their functions and binding partners are not fully understood even after decades of research. Functionalised cofactor mimics that bind in place of the unmodified cofactor can provide answers, as well as expand the scope of cofactor activity. Through chemical proteomics approaches such as activity-based protein profiling, the interactome and localisation of the native cofactor in its physiological environment can be deciphered and previously un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 166 publications
0
16
0
4
Order By: Relevance
“…Apart from modifying antibiotics themselves to render them tools, bacterial metabolites, signaling molecules, and other cellular components (here referred to as bacterial components) Please do not adjust margins Please do not adjust margins that are involved in resistance development can be used as templates for chemical tools as well. 21 Popular approaches follow a similar trend as compared to modified antibiotic and include the use of fluorescently labeled metabolites, photoaffinity metabolite analogues and activatable bacterial components.…”
Section: Modified Bacterial Components As Chemical Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from modifying antibiotics themselves to render them tools, bacterial metabolites, signaling molecules, and other cellular components (here referred to as bacterial components) Please do not adjust margins Please do not adjust margins that are involved in resistance development can be used as templates for chemical tools as well. 21 Popular approaches follow a similar trend as compared to modified antibiotic and include the use of fluorescently labeled metabolites, photoaffinity metabolite analogues and activatable bacterial components.…”
Section: Modified Bacterial Components As Chemical Toolsmentioning
confidence: 99%
“…Many innovative chemical approaches have been reported that have led to a plethora of new insights into resistance and how to potentially deal with this global threat. 18 For example, fluorogenic β-lactam probes are helping to understand β-lactamase activity and its involvement in resistance 19 while proteomic experiments with photoaffinity labels have helped identify new potential antibacterial targets [20][21][22] (vide infra).…”
Section: Introductionmentioning
confidence: 99%
“…Chemisch proteomische Ansätze zur Untersuchung von Proteinbindungspartnern anderer Cofaktoren als Häm sind bereits etabliert und wurden kürzlich veröffentlicht. [34] In dieser Arbeit wird eine ähnliche Strategie angewandt, beginnend mit der Entwicklung und Synthese von Häm-Sonden, die metabolisch in lebende Zielzellen aufgenommen werden können. Die Sonden wurden so konzipiert, dass sie reaktive "Klick"-Gruppen enthalten, die eine Anreicherung des Sonden-HBP-Komplexes nach der Aufnahme in die Zielzellen ermöglichen.…”
Section: Ergebnisse Und Diskussionunclassified
“…Functionalized cofactor mimics of pyridoxal containing an alkyne have ingeniously been developed by the Sieber group [24] and used to study PLP‐DEs in Gram‐positive Staphylococcus aureus , [25] Gram‐negative Escherichia coli and Pseudomonas aeruginosa , [26] and eukaryotic cells [27] . The alkyne handle is cleverly added directly to the pyridoxal itself, which must be phosphorylated, requiring the use of customized cell lines that are no longer capable of biosynthesizing their own PLP, and able to phosphorylate the probe in vivo by using an organism‐specific pyridoxal kinase (Scheme 2A).…”
Section: Introductionmentioning
confidence: 99%